A20 promoted the phagocytosis of lymphoma cells by dendritic cells from activated B-cell-like non-Hodgkin lymphoma: Effects of A20 on the phagocytosis of lymphoma cells - Ha, Nguyen Trong; Trang, Do Thi; Nhat, Pham Viet; Huong, Pham Thi; Giang, Nguyen Hoang; Mao, Can Van; Binh, Vu Duc; Vuong, Nguyen Ba; Xuan, Nguyen Thi (Cellular and Molecular Biology, 2024)
Non-Hodgkin lymphoma (NHL) is a lymphoproliferative disorder derived from either B or T lymphocytes. Among NHL, activated B-cell-like (ABC) diffuse large B-cell lymphoma (DLBCL) and T cell non-Hodgkin lymphomas (T-NHL) are poor prognosis and aggressive subtypes. Macrophages are professional phagocytic cells and dendritic cells (DCs) are professional antigen-presenting cells in immune system. Doxorubicin (Dox) and Etoposide (ET) are the most effective anti-cancer drugs. A20 and CYLD are negative regulators of NF-κB-dependent functions in many cell types. Little is known about the roles of A20 and CYLD in regulating functions of DCs and macrophages from NHL. The present study, therefore, explored whether A20/CYLD expression contributes to functions of DCs and macrophages from NHL. To this end, blood samples of seventy-nine patients with ABC DLBCL and T-NHL were examined. Gene expression profile was determined by quantitative RT-PCR and immunophenotype, cell apoptosis and phagocytosis by flow cytometry. As a result, immunophenotypic analysis showed that the numbers of CD13+CD117-, CD56+CD40+ and CD23+CD40+ expressing cells were significantly elevated in ABC DLBCL cases compared to healthy individuals and T-NHL patients. Interestingly, upon treatment of Dox and ET, the phagocytosis of lymphoma cells was significantly reduced by CD11c+CD123- DCs and the percentage of CD56+ mature DCs was significantly enhanced in ABC DLBCL patients only in the presence of A20 siRNA, but not CYLD siRNA. In conclusion, ABC DLBCL patients with low A20 expression were defective in elimination of lymphoma cells by DCs and linked to killer DC expansion in circulation.